The Role of Work Empowerment, Work Motivation, and Work Environment in Improving Employee Performance in the Textile Industry in Ungaran (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
The structural contraction in the Indonesian textile industry raises critical questions about the sustainability of the sector and the drivers of employee performance in the current manufacturing sector. This study examines how work empowerment, work motivation, and the work environment influence employee performance among textile workers in Ungaran, Central Java. The study used cross-sectional survey data and analyzed them using multiple linear regression. All research instrument items were found to be valid and demonstrated a very high level of reliability. Furthermore, classical assumption tests confirmed that the data were normally distributed and free from multicollinearity and heteroscedasticity. The results showed that all three predictor variables had a positive and significant influence on employee performance. Work motivation emerged as the strongest predictor, followed by work environment and work empowerment. Simultaneously, these three variables were also able to explain a significant portion of the variance in employee performance. Furthermore, the study identified a structural-psychological gap in work empowerment: the meaning and competence dimensions were strong, while the self-determination and impact dimensions were consistently weaker. This suggests that a centralized authority structure limits employee performance potential. These findings extend the psychological empowerment model and Self-Determination Theory to the crisis-affected manufacturing sector, and provide evidence-based guidance for integrated performance management in the Indonesian textile industry.